Functional Analysis of Three Unusual Assemblages from the Cape Dorset Area, Baffin Island - Arundale, Wendy Hanford (ARCTIC, 1980)
A brief survey of the Cape Dorset area, Baffin Island recovered surface collections from three very similar, but unusual quartz assemblages. This paper hypothesizes that these assemblages represent a consistent set of activities. In testing this hypothesis, the author uses an approach to functional analysis that has several important advantages over other methods. This approach can help solve problems in eastern arctic prehistory involving a relationship between environmental change and cultural change.